Life-cycle-cost-analysis for the seismic retrofitting and sustainability of existing building-stocks - Kyriakides, Nicholas; Chrysostomou, Christis; Tantele, Elia; Votsis, Renos; Charalambous, George (My University, 2016)
The quantification of the devastating effects of earthquakes on buildings can be achieved with the use of earthquake risk assessment. The formulation of strategies to minimise this risk is a complex task which relies on data regarding mainly the hazard, vulnerability and remaining life of the building. In this paper, the case study of Limassol municipality is presented. Initially, the building inventory and categorisation is defined followed by the selection of hazard scenarios and the development of analytical vulnerability curves. In the final part, risk assessment is performed leading to the formulation of retrofitting strategies for long term use. Based on the results from the life-cycle cost assessment the following conclusions can be drawn: 1) decision making regarding pre-earthquake strengthening, is an inherently multidisciplinary task and the required data was collected from a wide variety of sources after rather strenuous efforts, 2) decisions regarding the seismic rehabilitation of existing buildings require both engineering and economic studies and consideration of social priorities, and 3) it was observed that human casualties influence considerably the optimum retrofit level. The reference value used of €500,000 is an upper bound by the Greek standards, but it is a rather conservative value for other western countries (e.g. the US). Nevertheless the inclusion of the cost of human fatalities increased considerably the required retrofit level for both building categories. In any case, protection of life is undoubtedly the primary criterion for pre-earthquake retrofitting. © fédération internationale du béton (fib).
Keywords: Life-cycle cost assessment; Optimum retrofit level; Fragility curves